Three essays in wage differentials: inequality growth, education standards, and immigration - Gao, Yuan (Kansas State University, 2009)
This dissertation consists of three essays focusing on wage inequality and education policy. Essay 1 considers growth in the variance of wages. Prior work has documented that the college premium plays a major role in explaining wage variance growth. This essay examines the extent to which this role can be attributed to an increase in the dispersion of occupation-specific returns to post-secondary education. Using the variance components approach and CPS data between 1979-1981 and 2003-2005, the essay shows that the variation in the college premium across occupations has increased over time, and this variation expansion explains about five percent of the growth in wage variance across the two periods. By dividing the sample workforce into professional and nonprofessional groups, the results suggest that the increased variation in the return to post-secondary education particularly caused the wage gap between the professional and non-professional workers to increase. Essay 2 applies quantile regression methodology to the study of the determinants of the wage distribution among natives and immigrants in the U.S., using PUMS from 1990 and 2000, and ACS from 2006. Among other findings, the immigrant/native wage gap is concentrated at the lower end to the median of the wage distribution, and the primary source of the wage gap is the relative lack of labor market skills among immigrants. A cross-time comparison shows that the recent immigrant/native wage gap after controlling for skill variables first decreased from 1990 to 2000 and then expanded from 2000 to 2006. The growth is concentrated at the two ends of the wage distribution, and the reason for growth is that the recent immigrants in 2006 are younger and thus have less market experience than their counterparts of 1990. Essay 3 is coauthored with Dr. Blankenau. We analyze the impact of changes in college admission standards on the skilled labor distribution, skilled firm distribution, and the match of skilled labor with skilled firms. We propose a model of schooling with heterogeneous labor and firms, in which firms’ decisions in creating skilled jobs are conditioned on the supply of skilled labor. The model shows that lowering standards without providing incentives to acquire skills does not necessarily motivate accumulation of human capital or expansion of skilled industry. Lower standards tend to create a mismatch of educated labor with unskilled positions. In some specifications, lower standards can lower firms’ willingness to create skilled positions, leaving more skilled workers underemployed.
Keywords: Wage Inequality; Education Standards; Immigration; Economics, Labor (0510)